A randomized controlled trial of the Happy, Healthy, Loved personalized text-message program for new parent couples: impact on breastfeeding self-efficacy and mood - Erin Henshaw; Marie Cooper; Teresa Wood; Sanchita Krishna; Marie Lockhart; Stacey Doan (BMC, 2024)
Abstract Background Breastfeeding self-efficacy has been identified as an important influence on breastfeeding outcomes. Among new parent couples, partners are uniquely positioned to be sources of support for developing breastfeeding self-efficacy, yet few breastfeeding programs have attempted to involve partners directly. The purpose of this study was to test the impact of a novel program, Happy, Healthy, Loved, on breastfeeding self-efficacy and maternal mood through emphasizing partner support and actively addressing postpartum-specific stress management in a tailored text message delivery program. Methods A randomized trial was conducted in which primiparous mother-partner dyads intending to exclusively breastfeed were recruited at midwestern hospitals 2-3 days after delivery. The clinical trial was pre-registered at clinicaltrials.gov (#NCT04578925, registration date 7/24/2020). Couples were randomized to receive intervention or an attentional control. Couples randomized to the intervention group then completed a brief interactive educational tablet program together (Happy, Healthy, Loved), followed by 6 weeks of tailored text messages providing reminders, coping strategies, and motivational milestones to improve breastfeeding self-efficacy. Participants in the control group received usual care followed by 6 weeks of attentional control text messages about infant development. Surveys were delivered at baseline, 6 weeks, and 6 months postpartum to both mother and partner to assess breastfeeding self-efficacy, mood, and social support (n = 62 couples). Results Outcomes of ANCOVA with baseline self-efficacy as a covariate showed a significant effect of intervention on 6 months breastfeeding self-efficacy when compared to control group. No other significant differences were found at 6 weeks or 6 months postpartum in breastfeeding self-efficacy, depressive or anxious symptoms. Conclusions Results of the present investigation suggest that a text-based dyad intervention improved breastfeeding self-efficacy at 6 months, but not 6 weeks, postpartum, indicating that text-based mother-partner interventions are a promising direction to continue exploring in postpartum health research. Trial registration Clinicaltrials.gov #NCT04578925.